CORRECTION OF RISK FACTORS IN OVERWEIGHT PATIENTS WITH ARTERIAL HYPERTENSION - A. M. Shilov; M. V. Melnik; A. O. Osiya; M. S. Dulaeva (Сеченовский вестник)
Therapeutic approaches to treatment of patients with obesity and arterial hypertension are discussed